Ocorrência de bactérias endofíticas associadas à quinoa com potencial de promoção do crescimento de plantas - Andrioli, Katia Kabroski (2016)
Quinoa is a food crop that has received great importance for the high nutritional value in proteins and amino acids. Endophytic bacteria inhabit the interior of plant tissues and promote direct and indirect benefits to plants. The association between quinoa and endophytic bacteria has not been studied. The aim of this study was to evaluate the occurrence of endophytic bacteria with potential for plant growth promotion associated with quinoa plants. The quinoa seeds were seeding in arable and forest soil in Entre Rios do Oeste and Toledo. The isolation was done 40 days after the seed germination, using quinoa roots as baits. The 10-2 to 10-7 dilutions were plated on solid media and inoculated into semi-solid media, both semi-specific and N-free. From the semi-solid media, the count was performed employing the method of the Most Probable Number (MPN). The phosphate solubilization test and the indol-acetic acid (IAA) phytohormone production in the isolates were performed to characterize the plant growth promoting. We obtained 130 colonies of endophytic bacteria, these, seven from the semi-solid media. The MPN ranged from not detected to 1,5x105cells per g-1 root. We observed a large morphological diversity from the phenotypic characterization and there was the formation of 14 groups to 70% of dissimilarity. All bacteria produced IAA in greater or lesser amount with the range of 0.90 to 63.42 μg mg-1 of protein. However, only 40% of the isolates showed phosphate solubilization halo. The morphophysiological characterization enabled to group the isolates with similar traits and the growth promotion tests have identified promising isolates for field tests